Development of Pop-Up Creative Educational Books to Improve Students' Critical Thinking in Science Lessons for Grade V Students at SDN Sumurjalak II 2022/2023: Pengembangan Buku Edukasi Kreatif Pop-Up Untuk Meningkatkan Berfikir Kritis Siswa Dalam Pelajaran IPA Siswa Kelas V Di SDN Sumurjalak II 2022/2023 - Hidayati, Ninik (Madrosatuna: Journal of Islamic Elementary School, 2024)
There is no learning media that can be used by educators in the teaching and learning process in science subjects, especially in single and mixed substances. In previous years educators only utilized teacher handbooks, student books, lecture methods and image media only. So that students become less interested in science subjects, especially in single and mixed substances. Based on the background of the above problems, this study is expected to provide Objectives (1) To determine the development of Pop-Up creative educational books in science subjects for grade V students at SDN Sumurjalak II, (2) To determine the ability of critical thinking skills of grade V students at SDN Sumurjalak II, (3) To determine the increase in the thinking ability of grade V at SDN Sumurjalak II in science subjects in the use of Pop-Up creative educational books. This research uses a research and development (R&D) approach with descriptive analysis of data that has been collected through interviews, questionnaires, tests and documentation methods. The researcher applied a procedural development model that refers to the research model developed by Borg & Gall, which was then modified by the researcher into a simpler, easier to implement and practical development model. The following is a modified model that is used as a reference in this study which consists of four stages, namely the needs analysis stage, planning, product development, and product evaluation.